Dual gold(I)-catalyzed cyclization of dialkynyl pyridinium salts - Tšupova, Svetlana; Cadu, Alban; Stuck, Fabian; Rominger, Frank; Rudolph, Matthias; Hashmi, A. Stephen K. (ChemCatChem, 2017)
Novel dialkynyl pyridines were synthesized and protected as alkyl salts for dual gold(I)-catalyzed cycloisomerization. Different alkyl groups and counter ions were screened for the salts, with benzyl and hexafluorophosphate providing the best results. The cyclization led to NMR yields of >95 % being obtained for a number of substrates. Step-wise hydrogenation of products could be performed in one-pot by Pd/C, with selective reduction of the double bonds, followed by deprotection of the benzyl group.